Hidroponik Keluarga: Estimasi Biaya Instalasi - Identiti Identiti; Pelican Landri; Asra Inkesar (Jurnal Pengabdian Kepada Masyarakat, 2025)
The demand for healthy food is increasing, yet limited urban land poses a challenge for families in Pekanbaru. This community service program aimed to enhance the capacity of pre-retirement, retired, and productive-age families in developing household hydroponics using the Floating Raft System. A participatory approach and hands-on practice were applied through training, hydroponic farm observation, and installation cost simulation. The results show that participants gained skills in hydroponic cultivation, estimated initial investment costs, and recognized its dual benefits: healthy consumption and additional household income. The program not only provided technical skills but also strengthened food self-sufficiency, improved nutritional awareness, and created opportunities for economic resilience. By involving family members across generations, household hydroponics serves as both a food security education tool and a sustainable solution for urban communities.